The Impact of Group Drumming Workshops on Teacher Wellbeing in a Primary School Setting - A Case Study - Curran, Orlaith (Trinity College (Dublin, Ireland). School of Education, 2021)
There is a growing interest in the use of collaborative arts activities to enhance wellbeing. This study aims to investigate the impact of group drumming sessions on teacher wellbeing in an educative setting. The research was a case study in design and took place in the researcher’s own school over a period of three weeks. Workshops were facilitated by Simeon Smith, from MaSamba. Pre- and post-workshop questionnaires were distributed to participants and seven teachers were interviewed at the conclusion of the three sessions. Positive outcomes were reported following completion of the workshops and findings were analysed within Seligman’s PERMA wellbeing framework (Seligman, 2011). There is a paucity of studies relating to research in the field of teacher wellbeing and group music making and this case study is a good starting point from where to begin to develop further research
Keywords: Music in Education; Education